Transparency in international law - Bianchi, Andrea; Peters, Anne, 1964- (Cambridge : Cambridge University Press, 2013)
'While its importance in domestic law has long been acknowledged, transparency has until now remained largely unexplored in international law. This study of transparency issues in key areas such as international economic law, environmental law, human rights law and humanitarian law brings together new and important insights on this pressing issue. Contributors explore the framing and content of transparency in their respective fields with regard to proceedings, institutions, law-making processes and legal culture, and a selection of cross-cutting essays completes the study by examining transparency in international law-making and adjudication.'--pub. desc.
Introduction; 1. On power and illusion: the concept of transparency in international law / Andrea Bianchi; Part I. International Environmental Law: 2. Transparency and international environmental institutions / Jutta Brunnee and Ellen Hey; 3. Global or European only?: International law on transparency in environmental matters for members of the public / Jonas Ebbesson; Part II. International Economic Law: 4. Transparency in international financial institutions / Luis Hinojosa Martinez; 5. Institutional transparency in the WTO / Panagiotis Delimatsis; 6. Transparency in international investment law: the good, the bad, and the murky / Julie Maupin; 7. Transparency and exchange of information in international taxation / Carlo Garbarino and Sebastiano Garufi; 8. Transparency and intellectual property protection in international law / Thomas Cottier and Michelangelo Temmerman; Part III. International Human Rights Law: 9. The human right to information as a vehicle for transparency / Jonathan Klaaren; 10. Transparency at home: how well do governments share human rights information with citizens? / Cosette Creamer and Beth A. Simmons; Part IV. International Health Law: 11. Institutional transparency in global health law-making: the World Health Organization and the implementation of the international health regulations / Emily Bruemmer and Allyn Taylor; Part V. International Humanitarian Law: 12. Behind the flag of Dunant: secrecy and the compliance mission of the International Committee of the Red Cross / Steven R. Ratner; 13. How much secrecy does warfare need? / Orna Ben-Naftali and Roy Peled; Part VI. International Peace and Security Law: 14. Transparency in the Security Council / Antonios Tzanakopoulos; 15. Transparency as a cornerstone of disarmament and non-proliferation regimes / Mirko Sossai; Part VII. Cross-cutting Issues: 16. Transparency in international law-making / Alan Boyle and Kasey McCall-Smith; 17. Transparency in international adjudication / Thore Neumann and Bruno Simma; 18. Transparency and business in international law: governance between norm and technique / Larry Cata Backer; 19. Power and the public: the nature and effects of formal transparency policies in global governance institutions / Megan Donaldson and Benedict Kingsbury; Conclusion: 20. Towards transparency as a global norm / Anne Peters.
Includes bibliographical references and index.
Keywords: Government liability (International law); Transparency in government -- Law and legislation; International economic relations; Freedom of information